Molecule Sensing: Sculpting Extreme Electromagnetic Field Enhancement in Free Space for Molecule Sensing (Small 33/2018). Issue 33 (16th August 2018) - Liu, Fanxin; Song, Boxiang; Su, Guangxu; Liang, Owen; Zhan, Peng; Wang, Han; Wu, Wei; Xie, Yahong; Wang, Zhenlin
Abstract : In article number1801146, Peng Zhan, Wei Wu, Zhenlin Wang, and co‐workers create a plasmonic nanostructure through a unique process using ultrathin tetrahedral amorphous carbon deposition and nanofingers collapse, which enables the precise tailoring of the gap plasmon modes to realize strong spill‐out of the enhanced electromagnetic field. The resulting gap plasmon device can achieve chemical detection at the single‐molecular level while having high areal density of hotspots in free space.